A Belgian consensus strategy to identify familial hypercholesterolaemia in the coronary care unit and its subsequent cascade screening and treatment: BEL-FaHST (The BELgium Familial Hypercholesterolaemia STrategy). (October 2018) - Descamps, Olivier S.; Van Caenegem, Olivier; Hermans, Michel P.; Balligand, Jean-Luc; Beauloye, Christophe; Bondue, Antoine; Carlier, Stéphane; Castermans, Emilie; Chenot, Fabien; Claeys, Marc; De Block, Christophe; de Leener, Anne; et al.
Abstract: Background and aims: Familial hypercholesterolaemia (FH) is an autosomal dominant lipoprotein disorder characterized by significant elevation of low-density lipoprotein cholesterol (LDL-C) and markedly increased risk of premature cardiovascular disease (CVD). Because of the very high coronary artery disease risk associated with this condition, the prevalence of FH among patients admitted for CVD outmatches many times the prevalence in the general population. Awareness of this disease is crucial for recognizing FH in the aftermath of a hospitalization of a patient with CVD, and also represents a unique opportunity to identify relatives of the index patient, who are unaware they have FH. This article aims to describe a feasible strategy to facilitate the detection and management of FH among patients hospitalized for CVD. Methods: A multidisciplinary national panel of lipidologists, cardiologists, endocrinologists and cardio-geneticists developed a three-step diagnostic algorithm, each step including three key aspects of diagnosis, treatment and family care. Results: A sequence of tasks was generated, starting with the process of suspecting FH amongst affected patients admitted for CVD, treating them to LDL-C target, finally culminating in extensive cascade-screening for FH in their family. Conceptually, the pathway is broken down into 3 phases to provide the treating physicians with a time-efficient chain of priorities. Conclusions: We emphasize the need for optimal collaboration between the various actors, starting with a "vigilant doctor" who actively develops the capability or framework to recognize potential FH patients, continuing with an "FH specialist", and finally involving the patient himself as "FH ambassador" to approach his/her family and facilitate cascade screening and subsequent treatment of relatives. Highlights: A strategy to facilitate the detection and management of FH among patients hospitalized for CVD.